2018
DOI: 10.2196/publichealth.7598
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Tweets Related to Radiation: Visualization Using Co-Occurring Networks

Abstract: BackgroundAfter the Fukushima Daiichi nuclear accident on March 11, 2011, interest in, and fear of, radiation increased among citizens. When such accidents occur, appropriate risk communication must provided by the government. It is therefore necessary to understand the fears of citizens in the days after such accidents.ObjectiveThis study aimed to identify the progression of people’s concerns, specifically fear, from a study of radiation-related tweets in the days after the Fukushima Daiichi nuclear accident.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In all these studies, various data mining tools, techniques and methodologies are used. One of the techniques widely used is social network analysis (SNA) (Rantasila et al 2018 ; Yagahara et al 2018 ), which allows knowledge to be generated according to the relational structure of virtual interactions (Morales-i-Gras 2020b ). In addition, increasingly sophisticated tools are being used to provide more precise answers to more complex realities.…”
Section: Twitter Data Mining and Nuclear Energymentioning
confidence: 99%
“…In all these studies, various data mining tools, techniques and methodologies are used. One of the techniques widely used is social network analysis (SNA) (Rantasila et al 2018 ; Yagahara et al 2018 ), which allows knowledge to be generated according to the relational structure of virtual interactions (Morales-i-Gras 2020b ). In addition, increasingly sophisticated tools are being used to provide more precise answers to more complex realities.…”
Section: Twitter Data Mining and Nuclear Energymentioning
confidence: 99%
“…Twitter is an important platform to study because it has the potential to shape mainstream news because tweets can be embedded in online news stories, as well as highlighted in traditional media (such as TV or radio), amplifying their reach. Health scares need to be studied in the context in which they occur, and one method of studying them is through the use of Twitter [10,16]. This is because Twitter provides citizens with a platform that permits the rapid sharing of public views and opinions and allows these views to become viral and highly shared, regardless of their factual truth; henceforth, this is an important and significant area to study.…”
Section: Introductionmentioning
confidence: 99%
“…Risk communication is valuable in eliminating these social anxieties, but studies have indicated that social media was not fully utilized at the time of the Fukushima accident [ 18 ]. Yagahara et al [ 19 ] analyzed tweets for 7 days from the day of the earthquake on March 11 until March 17 to examine the changes in interest in radiation among Japanese citizens. Their analysis was based on co-occurrence networks related to radiation as the accident’s situation progressed.…”
Section: Introductionmentioning
confidence: 99%